Penerapan Metode Simple Additive Weighting (SAW) dalam Penentuan Santri dengan Hafalan Terbaik - Dedy Mulyadi; Diana Nur Windasari (Sekolah Tinggi Ilmu Komputer Binaniaga, 2021)
Currently, the selection of students with the best memorization is carried out based on estimates or assumptions that students who are selected with the best memorization have met the predetermined criteria. The objectives of this research are: to get the priority of students' assessment based on the best memorization, to get an effective process in selecting students with the best memorization, to develop applications which are then measured for accuracy. The results of the level of accuracy from this research are: the level of accuracy according to users before application development is very inaccurate, the level of accuracy according to users after application development is very accurate, the level of accuracy according to experts or system experts before application development is very inaccurate accurate, the level of accuracy according to system experts after application development is very accurate. Meanwhile, the comparison test results obtained: there is a significant difference in the accuracy of the system of applying the Simple Additive Weighting (SAW) method to determine the students with the best memorization, according to users between before and after system development, and there is no difference in the accuracy of the system of applying the Simple Additive Weighting (SAW) method to determine the students with the best memorization, according to experts or system experts between before and after system development.